Migration and Remittances Factbook 2016, Third Edition - World Bank Group (Washington, DC: World Bank, 2016)
The Migration and Remittances Factbook 2016 attempts to present numbers and facts behind the stories of international migration and remittances, drawing on authoritative, publicly available data. It provides a snapshot of statistics on immigration, emigration, skilled emigration, and remittance flows for 210 countries and 15 regional and income groups. The Migration and Remittances Factbook 2016 updates the 2011 edition of the Factbook with additional data on bilateral migration and remittances and second generation diasporas, collected from various sources, including national censuses, labor force surveys, population registers, and other national sources.